Co-operative Detection for Malicious Nodes in Under-Attack WSN - Ranjan Vikas, Shweta; Priyalakshmi, B; Gautam, Nikita; Potti, Sairam (International Journal of Engineering and Technology, 2018)
The network security must be taken into consideration in wireless sensor networks. In our project, we take sensor node data falsification (SNDF) attack using malicious nodes and co-operative detection is used. Fusioncentre collects information from the nodes created in a cluster environment and makes a global decision. The protocol used here is Ad-hoc-on demand distance vector[5] (AODV) and the performance analysis is done using parameters such as throughput and End-to-end delay. The stimulation is done in NS2 using network animator and graphical results are taken.The throughput will be increased compared to the existing system whereas End-to-End delay will be decreased.Â Â